(untitled) (Bioscience Journal, 2016)
The aim of this study was to assess physiological parameters, hair coat morphological characteristics and temperature gradients in crossbred Holstein-Gyr cows in the municipality of Tapira, Minas Gerais (MG), Brazil. Forty-nine lactating cows from six Holstein (H) and Gyr (G) genetic groups (1/4H 3/4G, 3/8H 5/8G, 1/2H 1/2G, 5/8H 3/8G, 3/4H 1/4G and 7/8H 1/8G) were distributed in a completely randomized design. The dry-bulb temperature and relative humidity were recorded, and the temperature and humidity index (THI) was calculated. The rectal temperature, respiratory rate and body surface temperature were measured, as were hair thickness, numbers, length and angle. Cows with a greater than 50% Holstein breed ratio (5/8H 3/8G, 3/4H 1/4G and 7/8H 1/8G) showed a higher respiratory rate and greater hair length than animals with genetic composition equal to or greater than 50% Zebu (1/2H 1/2G, 3/8H 5/8G and 1/4H 3/4G). Animals from the 1/2 and 1/4 HG genetic groups showed the greatest hair angle (P<0.05). With respect to climatic characteristics, the examined locality was within the thermoneutral zone and therefore did not impose conditions of thermal stress. The animals exhibited thermoregulation and hair coat characteristics that were within physiological parameters.